Structural and Thermal Study of Mg2TiO4 Nanoparticles Synthesized by Mechanical Alloying Method - Bhuyan, Ranjan K.; Pamu, D.; Sahoo, Basanta K.; Sarangi, Ashish K. (Micro and Nanosystems, 2020)
Background: Mg2TiO4 – based ceramics have proven their potentiality in the field of wireless communication systems. In the past, Mg2TiO4 ceramics was considered a quite optical response material in thin film form. Moreover, there is very few studies have been done whatever the proposed work in the present study. Objective: To prepare Mg2TiO4 nano-powders with the help of High Energy Ball Mill (HEBM) and intend to investigate its effect on crystal structure, microstructure and on thermodynamic behavior of MgO-TiO2 system. Methods: Mg2TiO4 ceramics were synthesized using Mechanical alloying method from high- purity oxides MgO and TiO2 (99.99%) of Sigma Aldrich (St. Louis, MO). Results: From the experimental studies it is observed that the powder’s particle size decreases with an increase of milling time. XRD analysis is carried out for phase confirmation of the mixed Mg2TiO4 powder. Further, the result also showed that there is structural changes occurred in the sample by high energy ball milling process, milled at different times. The nanocrystalline nature Mg2TiO4 powder was confirmed from microstructure taken by Field Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM). Further, differential thermal gravimetric analysis has been carried out to investigate the thermal behavior of milled Mg2TiO4 -powder (35 hours). Conclusion: In work, the effect of mechanical alloying on structural, microstructural and thermal properties of nanocrystalline Mg2TiO4 powders has been investigated systematically. The effect of milling time on particle size, crystal structure and the microstructure was studied using XRD, FE-SEM, TEM and DSC/TGA analysis. The microstructural analysis (FE-SEM and TEM) reveals the nanocrystallinity nature of MTO ceramics prepared by mechanical alloying method. The thermal decomposition behavior of the milled powders was examined by a Thermo-Gravimetric Analyzer (TGA) in argon atmosphere.
Keywords: XRD